Islamic Religious Education in the Digital Era: Learning with Multimedia Learning - Nafiatus Syauqi; Faaiq Labibatul Ilmi; Nala Shofia; Mubarok Ahmadi (Al-Hukumah: Jurnal Ilmu Pemerintahan dan Studi Islam, 2026)
This study aims to examine the role, urgency, and benefits of multimedia learning in Islamic Religious Education (PAI) in the digital era, as well as to identify the challenges and management strategies to ensure its alignment with Islamic values. The research employs a library research method by analyzing relevant scientific sources, including books, journals, and scholarly articles related to learning media, multimedia learning, and Islamic education. The findings indicate that multimedia learning enhances students’ interest, participation, and understanding of PAI materials through more interactive, flexible, and meaningful learning experiences, while also supporting the development of students’ digital literacy. However, the use of multimedia may also lead to negative impacts, such as technological dependency, decreased concentration, and exposure to inappropriate content if not properly supervised. In conclusion, multimedia learning is highly effective in PAI instruction when it is carefully designed, well-controlled, and integrated with the reinforcement of moral and spiritual values, thereby improving learning outcomes and fostering students’ character and Islamic ethics.